Why Does H Demand the Guarding of YHWH’s Sabbaths, Respecting of Elders and Reprimanding of Compatriots? - Adam, Klaus-Peter (Journal of Hebrew Scriptures, 2024)
Among the commands of H, elderly honor, Sabbath observance, and mutual reprimanding of compatriots are hallmarks. The origin, genre, and a comparable legal framework of these sentences can be found in what was labeled rules of (local) religious associations known from demotic papyri, from the Fayum going back to the 6th century BCE. In a tone comparable to a constitutional legislation, H is seen as an analogy for the rules of conflict settlement of local communities: it seeks to keep out governmental authority from local affairs, stipulates the respective festival day, and claims jurisdiction for its local community. All of these are also key elements of H’s anti-Persian stance. Read as a constitutional law of local bulwarks fending off central governmental authority in Egypt, the rules of local religious associations provide a hermeneutical lens for an analogous historical reading of H as "constitutional law." H in Lev 19:3-4, 11-18, 30—as a document of the priestly community in Yehud—would strengthen local institutions, including the arbitrarily stipulated festival day at the sanctuary, the elders as local institution, and internal jurisdiction of a priestly community bolstering itself as a bulwark against transgressions of the Achaemenid empire.